Guilt by degrees : a novel - Clark, Marcia (Clark, Marcia. Rachel Knight novel., 2012)
Deputy district attorney Rachel Knight takes the case of a murdered homeless man, over the objections of potentially backstabbing rivals. With the help of Detective Bailey Keller, she finds a missing piece of the puzzle, and realizes that the case is connected to the vicious murder of a LAPD cop a year earlier. The primary suspect in that case had been acquitted, but now Rachel and Bailey are hot on the trail of new leads.